Steganography and Audio Cryptography Fusion with Enhanced LSB For Secure Data Hiding in Spatial Domain (International Journal of Scientific Research in Science and Technology, 2024)
The growing need for secure data transmission and storage has prompted the convergence of steganography and audio cryptography techniques. This project introduces a novel approach that amalgamates these methods to achieve heightened data security. The focus lies in integrating the Enhanced Least Significant Bit (LSB) replacement algorithm within the spatial domain, enhancing the concealment efficacy. Steganography, an artful practice of concealing information within seemingly innocuous carrier mediums, is combined synergistically with audio cryptography, which encrypts data for secure transmission over auditory channels. Leveraging the amalgamation of these methods results in a robust framework for data hiding, ensuring confidentiality and integrity. The utilization of the Enhanced LSB algorithm within the spatial domain strengthens the concealment process, optimizing the embedding capacity while maintaining imperceptibility. This method enhances the resilience against detection and ensures a higher level of security for the embedded data. The paper presents a detailed analysis of the fusion approach, providing insights into its effectiveness, capacity, and computational feasibility. Furthermore, experimental results demonstrate the enhanced security achieved through the proposed fusion technique, affirming its potential for secure data hiding applications in various domains. In conclusion, the fusion of steganography and audio cryptography coupled with Enhanced LSB within the spatial domain offers a promising paradigm for safeguarding sensitive information, catering to the escalating demands of secure data transmission and storage.